ANALISIS PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA PENGOLAHAN TISU DI DEPARTEMEN PAPER MACHINE 11 PT. PINDO DELI PULP AND PAPER MILLS 2 - Rizky Eka Triana (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
Based on Health Law No. 36 of 2009 article 164 regarding occupational health, it is explained that occupational health efforts are aimed at protecting workers so that they live healthy and avoid health problems and bad effects caused by work, and recovery and bear all the costs of maintaining the health of workers. The protection is intended so that workers can safely carry out their daily work to increase national production and productivity. Workers must obtain protection from various problems around and on themselves that can override and interfere with themselves and their implementation. According to the Occupational Safety and Health Administration (OSHA), Personal Protective Equipment (PPE) or personal protective equipment (PPE) is defined as a tool used to protect workers from injury or illness caused by contact with hazards in the workplace, either chemical, biological, radiation, physical, electrical, mechanical and others. PT. Pindo Deli Pulp Paper Products is a large national private paper industry located in Kuta Mekar Village Btb. 69 Ciampel, Karawang, West Java, Indonesia. The performance of the use of PPE for shoes is good, the type of mask is good, the type of helmet is quite good, the type of ear plug and gloves is not good.